Effects of hypoxia-inducible factor prolyl hydroxylase inhibitors versus erythropoiesis-stimulating agents on iron metabolism and inflammation in patients undergoing dialysis: A systematic review and meta-analysis. Issue 4 (April 2023) - Zheng, Qiyan; Zhang, Pingna; Yang, Huisheng; Geng, Yunling; Tang, Jingyi; Kang, Yi; Qi, Airong; Li, Shunmin
Abstract: Aims: This study aimed to evaluate the effects of hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs) on iron metabolism and inflammation in dialysis-dependent chronic kidney disease (DD-CKD) patients. Methods: PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov websites were searched for randomized controlled trials (RCTs) investigating HIF-PHIs versus ESAs for DD-CKD patients. Key findings: Twenty studies with 14, 737 participants were included in the meta-analysis, which demonstrated no significant difference in the effect of transferrin saturation and ferritin between HIF-PHIs and the ESAs group (MD, 0.65; 95%CI, −0.45 to 1.75; very low certainty; SMD, −0.03; 95% CI, −0.13 to 0.07; low certainty). However, HIF-PHIs significantly increased the iron (MD, 2.30; 95% CI, 1.40 to 3.20; low certainty), total iron-binding capacity (SMD, 0.82; 95% CI, 0.66 to 0.98; low certainty), and transferrin (SMD, 0.90; 95%CI, 0.74 to 1.05; moderate certainty) levels when compared with the ESAs group. In contrast, the hepcidin level and dosage of intravenous iron were significantly decreased in the HIF-PHIs group compared with the ESAs group (MD, −15.06, 95%CI, −21.96 to −8.16; low certainty; MD, −18.07; 95% CI, −30.05 to −6.09; low certainty). The maintenance dose requirements of roxadustat were independent of baseline CRP or hsCRP levels with respect to the effect on inflammation. Significance: HIF-PHIs promote iron utilization and reduce the use of intravenous iron therapy. Furthermore, HIF-PHIs, such as roxadustat, maintain the erythropoietic response independent of the inflammatory state. Thus, HIF-PHIs may be an alternative treatment strategy for anemia in DD-CKD patients, where ESA is hyporesponsive due to iron deficiency and inflammation.